Pengaruh E-Trust dan Online Consumer Review Terhadap Keputusan Pembelian - Nuri Purwanto (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
This study aims to determine the effect of e-trust and online consumer reviews on the purchasing decisions of Tokopedia consumers in Jombang. This research is a type of verification research with a quantitative approach and using explanatory research methods. The data in this study include primary and secondary data, as well as for the population, namely Tokopedia consumers in Jombang, totaling 96 respondents. The sampling technique of this study used accidental sampling. The measurement scale uses a Likert scale, data collection uses a questionnaire with data analysis techniques using multiple linear regression analysis and processed using SPSS version 21. The results in this study show that e-trust and online consumer reviews have a significant effect on purchasing decisions. Thus, it can be concluded that e-trust and online consumer reviews affect the purchasing decisions of Tokopedia consumers in Jombang.).